2014
DOI: 10.1016/j.sbspro.2014.01.130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Driver Task-related Fatigue on Driving Performance

Abstract: In this study, passive task-related fatigue effects on highway driving were analyzed by means of driving simulator experiments. Ten drivers were asked to drive in various environments in the morning (9:00-11:00 a.m.) and early afternoon (1:00-3:00 p.m.). Mean of Absolute Steering Error and Standard Deviation of Lateral Position, calculated on sub-intervals of 4 minutes, were analysed as response variables. The results confirmed the negative influence of the duration of driving tasks and circadian effects on dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 25 publications
1
49
0
1
Order By: Relevance
“…Previous research has investigated the driving duration effect on physiological and performance decrement (Schleicher et al, 2008;Di Stasi et al, 2012;Wang & Pei, 2014;Gastaldi et al, 2014). However, most of the prior research has studied the effect of short driving duration, which is defined as below two hours (Schleicher et al, 2008;Di Stasi et al, 2012;Gastaldi et al, 2014). Wang and Pei (2014) investigated the effect of four hours of driving on performance measures; however, a study looking at the possibility of using other indicators has not yet been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has investigated the driving duration effect on physiological and performance decrement (Schleicher et al, 2008;Di Stasi et al, 2012;Wang & Pei, 2014;Gastaldi et al, 2014). However, most of the prior research has studied the effect of short driving duration, which is defined as below two hours (Schleicher et al, 2008;Di Stasi et al, 2012;Gastaldi et al, 2014). Wang and Pei (2014) investigated the effect of four hours of driving on performance measures; however, a study looking at the possibility of using other indicators has not yet been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Sobre las horas de conducción, diferentes estudios muestran resultados semejantes, donde el tiempo de conducción por lo general es mayor de 10 horas (14,15) , esto demuestra que la actividad laboral de los conductores es inversamente proporcional a sus horas de sueño, pudiendo ser este el motivo por el cual los conductores presenten excesiva somnolencia diurna; además, en el presente estudio la somnolencia diurna se podría atribuir al sistema de rotación, teniendo en consideración el turno laboral de cada uno de los conductores, como es el caso del estudio de Gastaldi et al (22) .…”
Section: Discussionunclassified
“…One of the most relevant processes related to driving behavior that is at risk is fatigue [31]. In the specific case of professional drivers, it has been shown that in the context of work, fatigue predicts a greater prevalence of occupational diseases (e.g.…”
Section: Introductionmentioning
confidence: 99%